Excitation dynamics in Photosystem I trapped in TiO(2) mesopores - Szewczyk, S. (Photosynth Res, 2020)
Excitation decay in closed Photosystem I (PSI) isolated from cyanobacterium Synechocystis sp. PCC 6803 and dissolved in a buffer solution occurs predominantly with a ~ 24-ps lifetime, as measured both by time-resolved fluorescence and transient absorption. The same PSI particles deposited in mesoporous matrix made of TiO(2) nanoparticles exhibit significantly accelerated excitation decay dominated by a ~ 6-ps component. Target analysis indicates that this acceleration is caused by ~ 50% increase of the rate constant of bulk Chls excitation quenching. As an effect of this increase, as much as ~ 70% of bulk Chls excitation is quenched before the establishment of equilibrium with the red Chls. Accelerated quenching may be caused by increased excitation trapping by the reaction center and/or quenching properties of the TiO(2) surface directly interacting with PSI Chls. Also properties of the PSI red Chls are affected by the deposition in the TiO(2) matrix: they become deeper traps due to an increase of their number and their oscillator strength is significantly reduced. These effects should be taken into account when constructing solar cells’ photoelectrodes composed of PSI and artificial matrices. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11120-020-00730-1) contains supplementary material, which is available to authorized users.